OROS Methylphenidate Long-Term Study in ADHD - J Gordon Millichap (Pediatric Neurology Briefs)
Once-daily osmotic controlled-release (OROS) methylphenidate (Concerta) in the treatment of 407 children, aged 6-13 years, with ADHD who were known MPH responders, was evaluated in a 24-month multicenter, open-label, nonrandomized study, and reported from the Massachusetts General Hospital, Boston.